2002
DOI: 10.1038/sj.eye.6700030
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity in the UK I: The organisation of services for screening and treatment

Abstract: Aims To ascertain how closely services for the screening and treatment of retinopathy of prematurity (ROP) were organised on a national level in 1995. Methods Questionnaires about the local arrangements for the screening and treatment of retinopathy of prematurity (ROP) were sent to the entire consultant membership (n = 648) of the Royal College of Ophthalmologists (RCOphth) and to the clinical directors (n = 259) of neonatal units and other units caring for preterm babies in the UK in 1995. Results 568/648 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
40
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 8 publications
0
40
0
1
Order By: Relevance
“…[1][2][3] In countries and regions with high human development levels, as designated by the United Nations Development Program, such as the United States, Canada, and Western Europe, ROP occurs almost exclusively in very low-birthweight babies, and blindness in premature babies is limited by screening protocols in the nursery that allow reliable detection and treatment of severe disease. [4][5][6][7][8][9][10][11] At present, however, the burden of ROP blindness has shifted to the moderately developed countries of Latin America and the former socialist economies. 5,[12][13][14] In these nations, classified as Medium Human Development Countries (MHDC), ROP is often the single most common preventable cause of childhood blindness, responsible for up to 60% of blindness in children in some countries.…”
mentioning
confidence: 99%
“…[1][2][3] In countries and regions with high human development levels, as designated by the United Nations Development Program, such as the United States, Canada, and Western Europe, ROP occurs almost exclusively in very low-birthweight babies, and blindness in premature babies is limited by screening protocols in the nursery that allow reliable detection and treatment of severe disease. [4][5][6][7][8][9][10][11] At present, however, the burden of ROP blindness has shifted to the moderately developed countries of Latin America and the former socialist economies. 5,[12][13][14] In these nations, classified as Medium Human Development Countries (MHDC), ROP is often the single most common preventable cause of childhood blindness, responsible for up to 60% of blindness in children in some countries.…”
mentioning
confidence: 99%
“…This topic is raised in this issue of Biology of the Neonate by Termote et al [8] , who rightly point out that screening consumes a considerable amount of ophthalmic expertise. This is certainly the case in the UK, as just under 2% babies screened require treatment [9] and it takes 39-55 examinations to detect a single case requiring treatment [9,10] -ineffi cient by any standards. The situation in MHDCs is rather different as many babies are simply not screened.…”
mentioning
confidence: 99%
“…8 The recent report of a national UK audit showed that many ophthalmologists are making a great contribution to ROP screening, and frequently without this being recognised in their job plans. 5 The report by Brennan et al in this 9 that the regionalisation of ROP services improves compliance with guidelines. So, now is the time to follow the excellent example of the Newcastle group to look hard at how we screen babies for ROP and to consider all aspects of service organisation, and promote concordance with clinicians and families, 10 so that it is really both effective and efficient.…”
mentioning
confidence: 99%
“…5 Brennan et al point out that each baby requires an average of 2.3 examinations and it takes an average of 39 examinations to detect each case of threshold ROPFnot very dissimilar from the estimate of 55 examinations per threshold case obtained from a national audit. 5 This low treatment yield represents a massive 'funnel effect', and it could be argued that this is not optimising skilled and expensive ophthalmic expertise, which might be better utilised for other more fruitful tasks. So, now is the time to seriously explore alternatives to screening by ophthalmologists.…”
mentioning
confidence: 99%